The Analysis of the Main Character Through Three-Dimensional Aspect and Characterization in the Novel “The Namesake” by Jhumpa Lahiri - Ni Kadek Sarinata Dewi; Putu Lirishati Soethama; I Wayan Mulyawan (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study is conducted to examine the three-dimensional aspects and characterization methods in The Namesake by Jhumpa Lahiri. The primary focus is placed on identifying how the main character, Gogol, is portrayed through these dimensions and what methods of characterization are applied to reflect his development. A qualitative descriptive method is used in this research, applying Lajos’s theory of three-dimensional aspects along with Burroway’s concepts of direct and indirect characterization to analyze the narrative data from the novel. Through the analysis, it is revealed that Gogol is portrayed as a character who undergoes a significant transformation throughout the story. In the early stage, he is shown as a 14-year-old who struggles with his identity and feels detached from himself. As the narrative progresses, a rebellious attitude is displayed by Gogol as he distances himself from his Bengali background. In the final stage of his life, after experiencing personal loss and emotional challenges, he undergoes a more profound reflection, leading to a greater appreciation for his cultural heritage. This transformation is portrayed through the use of both direct and indirect characterization methods, by which the emotional and cultural journey of an immigrant character is effectively conveyed.